The untethered soul : the journey beyond yourself - Singer, Michael A (Oakland, CA : New Harbinger Publications, 2007)
Presents advice on ways to free oneself from habitual thoughts, emotions, and energy patterns that limit one's consciousness
Awakening consciousness -- The voice inside your head -- Your inner roommate -- Who are you? -- The lucid self -- Experiencing energy -- Infinite energy -- The secrets of the spiritual heart -- Transcending the tendency to close -- Freeing yourself -- Let go now or fall -- Removing your inner thorn -- Stealing freedom for your soul -- Pain, the price of freedom -- Going beyond -- Taking down the walls -- Far, far beyond -- Letting go of false solidity -- Living life -- The path of unconditional happiness -- The spiritual path of non-resistance -- Contemplating death -- The secret of the middle way -- The loving eyes of God
"A copublication of New Harbinger Publications and Noetic Books"--T.p. verso
Includes bibliographical references
Keywords: Consciousness; Self